Questioning the Legality of Arrests Based on the Status of the Wanted Person List (DPO) to Ensure Legal Certainty - Imani, Helmi Doa; Kartika , Dewi; Aaliyah , Syahlaa; Waluyadi , Waluyadi; Romlahayati , Yanti (PT FORMOSA CENDEKIA GLOBAL, 2025)
Unlawful or juridically defective arrests can also cause detention to become unlawful, so that such actions are considered illegal and can harm the principles of legal certainty and human rights. This study analyzes the legality of arrests according to the Criminal Code against suspects with the status of Persons Wanted List (DPO), by comparing two pretrial decisions: Decision Number 10/Pid.Pra/2024/PN Bdg and Decision Number 2/Pid.Pra/2024/PN Cbn. The research method used in writing this article is a normative approach. The data type used from the Law and Pre-Trial Decision Number 10/PID.Pra/2024/PN Bdg and Pre-Trial Decision Number 2/Pid.Pra/2024/PN Cbn as the main data. As well as interviews, as supporting data. The data collection technique used was document and literature studies, while the analysis used qualitative methods. The results of the study showed that in Decision Number 10/Pid.Pra/2024/PN Bdg, the judge stated that the arrest was invalid because it was carried out without the permission of the Chief Justice and proof of urgency, and the DPO status of the applicant was considered legally defective because an official summons did not precede it. On the other hand, in Decision Number 2/Pid.Pra/2024/PN Cbn, the arrest was made based on the court's determination, but the pretrial application was declared null and void because the main case had been delegated. Hence, the DPO status and arrest legality were not substantially tested.